Perancangan Aplikasi Virtual Reality Sebagai Media Pembelajaran Sistem Tata Surya - Syani, Mamay; Rizky Hadiansyah , Muhammad; Ahmad Firdaus, Eryan; Mulyana, Dadan; Yudi Permana, Nana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
Learning media have now followed existing technological developments, ranging from print technology, audio visual, computers to technology that combines print technology with computers. Currently, educational media, the result of a combination of print technology and PC, can be realized with Virtual Reality (VR) technology media. Virtual Reality (VR) is a technology that allows users to relate to an area simulated by a PC, an actual area that is imitated or an area that is only in the imagination. Traditional learning as usual where only one interaction occurs makes learning at this time very monotonous, examples of this traditional learning are through pictures, books or even other projection tools. However, with the existence of learning media that utilizes Virtual Reality that is able to realize objects in the virtual world into the real world, it can replace these objects into 3D objects, so that educational procedures are not monotonous.